Tree rings reveal signs of Europe's sustainable forest management long before the first historical evidence - Muigg, Bernhard; Skiadaresis, Georgios; Tegel, Willy; Herzig, Franz; Krusic, Paul J; Schmidt, Uwe E; Büntgen, Ulf (Scientific reports, 2020)
To satisfy the increasing demand for wood in central Europe during medieval times, a new system of forest management was developed, one far superior to simple coppicing. The adoption of a sophisticated, Coppice-with-Standards (CWS) management practice created a two-storey forest structure that could provide fuelwood as well as construction timber. Here we present a dendrochronological study of actively managed CWS forests in northern Bavaria to detect the radial growth response to cyclical understorey harvesting in overstorey oaks (Quercus sp.), so-called standards. All modern standards exhibit rapid growth releases every circa 30 years, most likely caused by regular understorey management. We further analyse tree-ring width patterns in 2120 oak timbers from historical buildings and archaeological excavations in southern Germany and north-eastern France, dating between 300 and 2015 CE, and succeeded in identifying CWS growth patterns throughout the medieval period. Several potential CWS standards even date to the first millennium CE, suggesting CWS management has been in practice long before its first mention in historical documents. Our dendrochronological approach should be expanded routinely to indentify the signature of past forest management practices in archaeological and historical oak wood.